Labor Standards in the Global Economy: Issues for Investors - Rivoli, Pietra (Journal of business ethics, 2003)
In the mid-1990s, global labour standards emerged as a new and important are of concern for socially responsible investors, especially with respect to investments in the "problematic" footwear, apparel, and toy industries. In this paper, I elucidate the primary areas of concern for investors and discuss a framework for evaluating firms' labor standards performance. In addition, I argue that today's sweatshop debates follow closely those of centuries ago, with the standard economic defense of low wage manufacturing on the one hand, and the activists' protests against poor conditions and wages on the other. An examination of this historical context reveals a promising middle ground in this ongoing debate.